Enhance Security of AES Algorithm Based on S-Box - Alkhamery, Rawia; Alahmadi, Yasser; Alsorori, Mokhtar; Alassali, Saleh (International Journal of Computer Sciences and Engineering, 2021)
Advanced Encryption Standard (AES) is an approved encryption algorithm that has been used so far in many applications. A strength of AES algorithm depends on substitution box (S-Box) that is the main component to provide nonlinearity operations. Although AES algorithm has been proven to be the most secure algorithm to date, the advances in computer processing speed nowadays and the attempts to break such algorithm through the linear and differential cryptanalysis made it vulnerable to obsolescence. Therefore, the development of the algorithm is still ongoing especially for modification of the static nature of its S-Box. This paper proposes a method to improve the security of AES algorithm by suggesting treatment in the Substitution Box which is used to generate nonlinear relationship. Experimental results showed that the proposed method can enhance security of AES algorithm in the same condition of efficiency.